2022
DOI: 10.1093/asjof/ojac077
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Aesthetic Surgery: A Mini-Review

Abstract: The purpose of this summary is to outline the available research on the psychological factors associated with aesthetic surgery. Aesthetic procedures such as abdominoplasty, breast augmentation, face lift, and rhinoplasty are shown to have unique preoperative and postoperative psychological factors. Depression and anxiety may occur after aesthetic procedures with an increased incidence in patients with certain depression prone personality traits. The pre-existing psychology of patients is also an important con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The theoretical review demands that plastic surgeons gain a better understanding of their patients' psychological burdens during consultation to maximize mood benefits after surgery. 5,6 This helps inform and regulate postsurgery expectations, as well as reduce the likelihood of mental health issues arising. 19 Therefore, it is necessary to promote effective and assertive communication in the doctor/patient relationship, clarify what plastic surgery entails before and after the procedure, and educate on what can realistically be achieved physically in the patient's body to avoid conflicts with their over-expectations and misconceptions about the operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The theoretical review demands that plastic surgeons gain a better understanding of their patients' psychological burdens during consultation to maximize mood benefits after surgery. 5,6 This helps inform and regulate postsurgery expectations, as well as reduce the likelihood of mental health issues arising. 19 Therefore, it is necessary to promote effective and assertive communication in the doctor/patient relationship, clarify what plastic surgery entails before and after the procedure, and educate on what can realistically be achieved physically in the patient's body to avoid conflicts with their over-expectations and misconceptions about the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the presurgery evaluation of patients, it is essential that surgery is indicated for healthy and stable individuals from a psychological and physical standpoint, as the aim is to ensure the benefits of the intervention outweigh the risks involved. 5 , 6 Therefore, a baseline evaluation is important. Of the total number of individuals evaluated in the sample, it was found that none showed signs of anxiety, and only 3.3% of patients displayed pathological body discomfort, moderate depression, and risk of developing an ED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AI-generated responses provided insight into the emotional struggles that patients may encounter post-rhinoplasty, including feelings of unfamiliarity with their changed appearance. These emotional challenges are well-recognized in cosmetic surgery patients and underscore the significance of addressing patients' psychological well-being 9,10 . Surgeon-patient communication and psychological support were highlighted as essential components in managing emotional concerns.…”
Section: Emotional and Psychological Impactmentioning
confidence: 99%